2010
DOI: 10.1002/jbmr.121
|View full text |Cite
|
Sign up to set email alerts
|

GATA-3 transduces survival signals in osteoblasts through upregulation of bcl-x L gene expression

Abstract: GATA-3, a transcription factor, participates in regulating cell development, proliferation, and death. This study was aimed at evaluating the roles of GATA-3 in protecting osteoblasts against oxidative stress-induced apoptotic insults and their possible mechanisms. Pretreatment with nitric oxide (NO) for 24 hours protected osteoblasts, prepared from neonatal rat calvaria, against oxidative stressinduced apoptotic insults. Such protection involved enhancement of Bcl-X L messenger (m)RNA and protein syntheses an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
48
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 47 publications
6
48
0
Order By: Relevance
“…16 Osteoblasts play a central role in mediating bone formation. 2,3 Our present data revealed that chitosan nanofiber scaffolds stimulated growth of mouse osteosarcoma UMR-106 cells and mouse calvarial osteoblasts. Also, we further demonstrated that chitosan nanofibers significantly improved the growth and proliferation of human osteoblasts.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…16 Osteoblasts play a central role in mediating bone formation. 2,3 Our present data revealed that chitosan nanofiber scaffolds stimulated growth of mouse osteosarcoma UMR-106 cells and mouse calvarial osteoblasts. Also, we further demonstrated that chitosan nanofibers significantly improved the growth and proliferation of human osteoblasts.…”
Section: Discussionmentioning
confidence: 51%
“…Abbreviations: mrNa, messenger rNa; runx2, runt-related transcription factor 2; rT-Pcr, reverse transcription polymerase chain reaction. 3,9 An increase in ALP staining signals correspondingly indicates enhancement of osteoblast maturation. Such an effect of chitosan nanofibers on osteoblast development was also demonstrated by the Alizarin red-and von Kossa-staining assays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress is directly linked to estrogen decline and osteoporosis occurrence (Manolagas, 2010). Osteoblasts also mediate bone formation in bone remodeling but are easily insulted by oxidative stress (Ducy et al, 2000;Chen et al, 2010). Our previous studies reported that Kunze could protect osteoblasts from oxidative-and nitrosative stress-induced apoptotic injury (Liu et al, 2001;Huang et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…10,11 A variety of biomolecules participate in regulating inflammation-induced osteoblast injury. [12][13][14] Reducing such stress-caused damage can promote osteoblast maturation and bone healing. Our previous studies showed that Gusuibu, a traditional Preparation of the water extract of gusuibu (Weg) and nanoparticles of the Weg (nWeg).…”
Section: Introductionmentioning
confidence: 99%